Revisiting the Power Co-ordination Challenges of the Original Snowy Mountains Scheme - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2021)
The Snowy Mountains Scheme (1949–1972) was an Australian hydro-electricity generation triumph. However, the power co-ordination challenges were significant before the invention of fibre optic cable, as this historic paper from June 1964 attests.